Спорудження міжпромислових газопроводів для стабільного видобутку вуглеводнів - Воловецький, В. Б.; Щирба, О. М.; Volovetskyi, V. B.; Shchyrba, O. M. (Видавництво Львівської політехніки, 2019)
Розглянуто під’єднання міжпромислових газопроводів між об’єктами видобування вуглеводнів на Юліївському ЦВНГК. Проаналізовано стан міжпромислових газопроводів, якими транспортують газ із Скворцівського нафтогазоконденсатного родовища. Виконано розрахунки із визначення гідравлічної ефективності та об’єму забруднень у внутрішній порожнині міжпромислових газопроводів. Встановлено, що під час експлуатування міжпромислових газопроводів виникають ускладнення. пов’язані із накопиченням рідини у внутрішній порожнині, внаслідок чого зменшується обсяг протранспортованого газу та видобуток вуглеводнів. Для забезпечення надійного транспортування газу міжпромисловими газопроводами автори запропонували комплексні заходи, які передбачають збудування дотискувальної компресорної станції, зміну під’єднання наявного міжпромислового газопроводу та спорудження додаткового міжпромислового газопроводу.

The article deals with the existing system of gas pipelines between hydrocarbon production facilities at the Yuliivskyi oil and gas condensate production facility (YOGCPF). This system of gas pipelines ensures the flow of hydrocarbon raw materials from the wells of Narizhnianske, Yuliivske and Skvortsivske oil and gas condensate fields to the complex gas treatment unit (CGTU). The preliminary treatment of natural gas from mechanical impurities, liquid, hydrocarbon condensate and water is carried out at gas preparation plants of these fields. Gas treatment and the extraction of liquid hydrocarbons, condensate and propane-butane fractions are carried out at CGTU-2. Complex measures are proposed to optimize the operation of gas condensate wells of the Skvortsivske field and to prevent the accumulation of contaminations in the inner cavity of gas gathering pipelines. They predict construction of the booster compressor station, change of the connection of the existing gas gathering pipeline and construction of the additional gas gathering pipeline. The implementation of these measures will allow the reliable transportation of gas and stable hydrocarbon production. For the timely monitoring, it is proposed to install the control and measuring devices, such as pressure and temperature gauges, that will provide the automatic control of the parameters of gas gathering pipelines. In order to increase the efficiency of the operation of gas pipelines in case of liquid accumulation in the lower sections of the route, the authors propose the methods for the inner cavity cleaning, the injection of the solution of surfactants, the creation of high-speed gas flow, and the use of foam.
Construction of gas gathering pipelines for stable production of carbohydrates
Keywords: свердловина; газ; газопровід; видобування вуглеводнів; давачі тиску і температури; гідравлічна ефективність; well; gas; gas pipeline; hydrocarbons production; pressure and temperature gauges; 622.279